Envisioning the future of urban design from cinematic spaces: An exploration through science fiction films - Babaoğlu, Dila (Graduate School, 2025)
Studying the future involves exploring what lies ahead different from the past and present. When future studies are considered together with urban studies, the challenges of envisioning future cities become evident. As indicated in many contemporary urban studies, our cities face a range of issues—social, economic, environmental, governmental, and so on. Reconsidering existing cities' challenges and high urbanization rates, studying the urban future requires more and more attention nowadays. On the other hand, there are various visuals/images generated in envisioning the future of cities. Cinema, as a medium in representing various futuristic urban images and as a form of widely consumed artwork, plays a crucial role in envisioning the future. Films especially in science fiction genre portray many futuristic urban settings through cinematic spaces. This thesis aims to uncover insights from futuristic science fiction films in the study of future in urban design. In order to strengthen the relationship between the possible future settings conveyed through futuristic science fiction films and preferred settings of urban design in the future, science fiction films are explored. In this investigation, hidden/invisible clues of urban designs in cinematic spaces are revealed. It is explored how science fiction films adapt/present different urban design approaches. This thesis proposes how cinematic spaces can be instrumentalized in discussing the future of urban spaces. In order to conduct the investigation, two theoretical sections are organized to discuss how the future city is conceptualized in urban design field (Chapter 2) and to discuss how to read the cinematic representation of the city in cinema (Chapter 3). The exploration of the science fiction films is laid on two stages in Chapter 4 and Chapter 5. First stage is conducted in four phases to investigate the selected 70 science fiction films for their spatial and theoretical references to the future of urban design. At end of first stage, all films are categorized and 6 films are identified to focus on. In second stage of investigation in Chapter 5, selected 6 films are explored by using method of cinemetrics. Reconsidering cinematic spaces by collage, juxtaposition and superposition, the discussion of future urban space and design elements depicted in the sci-fi films is conducted scene by scene. Based on the aim and methodology above, Chapter 2 introduces a framework for studying the urban future. It emphasizes how the future is conceptualized in different fields such as technology, fashion, health in addition to urban studies. It defines science fiction and design fiction. It suggests that design fiction, which emerged in the mix of science fiction and science fact, is a convenient approach to evaluate the futuristic urban design settings from cinematic spaces in the discussion of the future of urban design. It highlights the role of diegetic representations of the urban space in cinematic spaces. Moreover, Chapter 2 provides an alternative reading of concepts developed for the future of space in urban design field. The conceptualization of the future space is grouped under three major groups: (I) designing the future cities originated from the past, (II) designing the future cities as a solution for the ambiguity of space and (III) considering the political motifs in generating futuristic urban concepts. In this chapter, it is concluded that none of these conceptions is singularly effective in approaching the future of urban design. Chapter 3 focuses on cinema and cinematic representation of space. It defines cinema as a type of mass media that is consumed and produced in the cities. It emphasizes how cinematic representation of space attracts various audiences as cine-tourists. Also, Chapter 3 introduces how cinematic space is defined in film studies and puts forward how cinematic representation of the space is convenient for exploring the urban space. Basic terms such as shot, scene and frame are defined in this chapter. Cinemetrics, as an advanced drawing system for representing the space is introduced. The case study of this thesis is comprised of five phases, which are given in Chapter 4 and Chapter 5. In the first phase, a film pool of 70 futuristic science fiction films is generated from the most cited films in the relevant disciplines about the representation of space. In the second phase, all of the films in the pool are reviewed to rediscover their references to the future of urban design. The films that entail spatial references for the future of urban design are converted into ideal drawings. In the third phase, the films are mapped according to their theoretical relevance to the concepts of the future space in urban design, introduced in Chapter 2. In the fourth phase of the investigation, the films are classified according to the time and visual content that they convey. 6 science fiction films, Equilibrium, Dredd, Cloud Atlas, Fifth Element, Logan's Run and Aeon Flux are identified and transferred to the fifth phase. In the fifth phase of the investigation beginning from Chapter 5, the selected 6 films are explored separately to reveal their spatial and theoretical references to contemplate the future of urban design from cinematic spaces. It is focused on how these films convey futuristic design ideas in addition to which clues of urban design they present. To understand how urban design clues are conveyed in the films, film tempo (average shot length) and proportion of scenes that present the urban design characteristic are referred to as supplementary aspects to be combined with the qualitative analysis of the cinematic spaces. To reveal which urban design clues are hidden in the cinematic spaces, scene by scene exploration is conducted with cinemetrics. It is decoded how these films portray various urban design characteristics of city elements, relying on the Lynch's image of the city. Squares, central meeting areas, city centers, streets, pathways, roads, other transportation lines, urban organization, site characteristics, buildings, man-made structures and activities are explored from futuristic urban settings in the cinematic spaces. Each films are reconsidered with which urban design concepts they adapt. It is concluded that 10 design concepts of Totalitarian Architecture, Natural Surveillance System proposed by Jane Jacobs, Acupuncture Urbanism developed by Sola Morales, Radiant City developed by Le Corbusier, Resilient City Concept, Collage City by Rowe and Koetter, Domed City by Fuller, Garden City Movement by Ebenezer Howard, Brutalist Architecture and City Beautiful Movement are adapted in these films. Based on the relationship between the films' release and concept's active period, it is revealed that film's adaptation of urban design concepts, movements and approaches provide evident clues to discuss the future of urban design. In the conclusion part, the thesis contribution to strengthen the link between the science fiction works and the future of urban design is emphasized. This chapter addresses the research questions and denote final remarks to be explored in further studies. Referring relationship between futuristic urban settings in science fiction films and the futuristic cities in the real world, it suggests that the futuristic representations of cities in the cinematic spaces are linked to the existing cities while the future of cities is linked to their futuristic representations in the films. Based on the outcomes generated from this thesis, it is believed that it contributes to strengthen the link between science fictional works particularly conveyed through cinematic spaces and the future of urban design via instrumentalization of cinematic space.
Kentsel tasarımın geleceğinin sinematik mekanlar aracılığıyla değerlendirilmesi: Bilim kurgu filmleri üzerinden bir keşif
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: science-fiction; bilim kurgu; urban design; kentsel tasarım; cinema; sinema; space; mekan